Rationale and design of a randomised, double-blind, placebo-controlled, parallel-group, investigator-initiated phase 2a study to investigate the efficacy and safety of elobixibat in combination with cholestyramine for non-alcoholic fatty liver disease - Atsushi Nakajima; Takeharu Yamanaka; Koji Yamamoto; Yasushi Honda; Kento Imajo; Masato Yoneda; Yuji Ogawa; Takaomi Kessoku; Takashi Kobayashi; Anna Ozaki; Satoru Saito; Michihiro Iwaki; et al. (BMJ Open)
Introduction Non-alcoholic fatty liver disease (NAFLD) pathogenesis involves abnormal metabolism of cholesterol and hepatic accumulation of toxic free-cholesterol. Elobixibat (EXB) inhibits the ileal bile acid (BA) transporter. EXB and cholestyramine (CTM) facilitate the removal of free cholesterol from the liver by decreasing BA recirculation to the liver, thereby stimulating novel BA synthesis from cholesterol. In this randomised, double-blind, placebo-controlled, parallel-group, phase IIa study, we aim to provide a proof-of-concept assessment by evaluating the efficacy and safety of EXB in combination with CTM in patients with NAFLD.Methods and analysis A total of 100 adult patients with NAFLD, diagnosed based on low-density lipoprotein cholesterol (LDL-C) level of >120 mg/dL and liver fat content of ≥8% by MRI-based proton density fat fraction (MRI-PDFF), who meet the inclusion/exclusion criteria will be enrolled. The patients will be randomly assigned to receive the combination therapy of 10 mg EXB and 9 g CTM powder (4 g CTM), 10 mg EXB monotherapy, 9 g CTM powder monotherapy or a placebo treatment (n=25 per group). Blood tests and MRIs will be performed 16 weeks following treatment initiation. The primary study endpoint will be the absolute LDL-C level change at week 16 after treatment initiation. The exploratory endpoint will include absolute changes in the liver fat fraction as measured by MRI-PDFF. This proof-of-concept study will determine whether the combination therapy of EXB and CTM is effective and safe for patients with NAFLD.Ethics and dissemination Ethics approval was obtained from the Ethics Committee of Yokohama City University Hospital before participant enrolment. The results of this study will be submitted for publication in international peer-reviewed journals and the key findings will be presented at international scientific conferences.Trial registration number NCT04235205